Sedative-Hypnotic Use in Patients with Borderline Personality Disorder and Axis II Comparison Subjects - Plante, David T. (2009)
Sleep disturbance is a common, yet poorly understood, phenomenon in borderline personality disorder (BPD). We examined the use of sedative-hypnotic medication in BPD, as part of a larger naturalistic study. In comparison to other personality disorder (OPD) comparison subjects, a significantly higher percentage of BPD subjects than OPD subjects used both as needed (prn) and standing medications to help them sleep. Specifically, over the course of the study, BPD subjects were approximately 4 times more likely to have used prn (OR = 4.27, 95% CI: 2.22–8.22) and standing sleeping medications (OR = 3.81, 95% CI: 1.88–7.72). When adjusted for differences in depression, anxiety, and age among BPD and OPD subjects, BPD subjects were approximately 3 times more likely to have used prn (adjusted OR = 3.38, 95% CI: 1.73–6.61) and standing sleeping medications (adjusted OR = 2.81, 95% CI: 1.33–5.95). These results indicate that sedative-hypnotic use is greater among BPD than OPD subjects. They also confirm clinical observations that subjective sleep disturbance is a significant problem in BPD.